Determination of the Physical Properties of the Protoplanetary Disk Around WW Cha Stars - Taha, Anas S.; Ahmed, Abdulla K.; Ali, Arshed (Iraqi Journal of Science, 2024)
The main goal of this work is to put a simple model of the spectral energy distribution of binary stars called WW Cha. This model is built up on the extracted data from various telescopes and archives for the target WW Cha stars and then analyzing them using a python environment. The result of the fitting proposes that there are two protoplanetary disks around the WW Cha star, with different physical properties for each disk, such as the size of the inner disk being 10 AU, while the size of the outer disk being 300 AU. The shape of the outer disk is a flaring disk not a flat disk according to the value of the power law for the surface density (1.5). The emission in the disk is caused by small amorphous olivine grains ranging in size from 0.1 to 3000 micrometers.